A study of hypertension epidemiology among urban population of Malwa region, India - Singhai, Abhishek; Punjabi, Aditya (International Journal of Research in Medical Sciences, 2016)
Background: Hypertension (HTN) is the leading risk factor for cardiovascular disease and mortality worldwide. Almost three quarters of individuals with HTN live in developing countries with limited health resources and where people have low awareness of HTN and limited access to health care. Our study was thus designed to determine the prevalence, awareness, treatment, and control rates of HTN. Methods: We conducted a cross-sectional survey in different areas of urban Indore. Inclusion criteria were adults older than 21 years who gave oral consent to participate. There were no exclusion criteria. Data were collected on demographic variables, socio-economic status, presence of other cardiovascular risk factors, and medication use. BP was measured after at least 10 minutes of rest in the sitting position. Data analysis was done with Statistical Product and Service Solutions (SPSS) Statistics version 17.0 (Chicago IL, USA). Results: From December 2014 to May 2015, a total of 1697 participants were enrolled in the study. Their mean age was 42.9 years and 56% were men. The crude prevalence of HTN in our study was 36.9%. The prevalence of HTN was higher in men compared with women and increased with increasing age groups. In addition, HTN was more prevalent in patients who smoked, patients with diabetes, patients with higher BMI, and those who were married, divorced, or widowed compared with singles. HTN awareness was 53%. Among “aware” participants, 93% were taking BP-lowering therapy. Among treated participants, 54% had their BP under control during the examination. This translates into an overall 27% control rate when all hypertensive patients were considered (treated and not treated). Conclusions: Our results confirm the importance of the HTN epidemic; only one third of participants have optimal BP levels and the remaining two thirds are either hypertensive or prehypertensive. Men in particular are severely affected by the disease: 43% and 35% have either HTN or pre-HTN. Their awareness, treatment, and overall control rates are lower than those of women.